Pengembangan Model Pembelajaran Mata Kuliah Pendidikan Multikultural Untuk Mahasiswa Pendidikan Guru Sekolah Dasar - Murniati Agustian (JTP - Jurnal Teknologi Pendidikan, 2014)
This reasearch aims to develop a model of multicultural education. The results of this reasearchs is the design of learning activities in the classroom. By using the media video in the above activity with make the student more interÂ¬ested because it matchs with the situation of students, so it helps the students understand the material. The tools of evalu- ation is relevant to the material, so then the students will able to think critically and re ec- tively. Self-learning moduls developed more easily to be understood, and the activities of self-learning are designed for more easily to be followed by students, so the objectives will be achieved successfully. The guidance of lecturers is made to help the lecturers implement multicultural education in the classroom.